Experimental study of the 197Au(n,2n) reaction cross section - Tsinganis, A.; Kokkoris, M.; Lagoyannis, A.; Mara, E.; Papadopoulos, C. T.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
In the present work, the 197Au(n,2n) reaction cross section is experimentally determined relative to the 27Al(n,α)24Na reaction at incident neutron energies of 9.0 to 10.5 MeV by means of the activation technique. The quasi-monoenergetic fast neutron beam was produced via the 2H(d,n)3He reaction at the 5.5 MV Tandem Van de Graaff accelerator at the NCSR “Demokritos” and was studied to determine the contribution of background “parasitic” neutrons using the multiple foil activation technique and the SULSA unfolding code. The cross sections for the population of the second isomeric state (12−) of 196Au and the sum of the ground (2−) and first isomeric state (5−) population cross sections were independently determined. Auxiliary Monte Carlo simulations were performed with the MCNP code.